2019
DOI: 10.1016/j.neuron.2019.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Plasticity of Higher-Order Thalamocortical Inputs during Sensory Learning

Abstract: Highlights d Mice learn a multi-whisker sensory association during automated home-cage training d Training, but not sensory stimulation alone, causes rapid synaptic plasticity in S1 d Synaptic plasticity observed only in higher-order thalamocortical pathways d POm thalamic inputs are strengthened sequentially, first on L5 and then on L2 Pyr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
128
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(139 citation statements)
references
References 61 publications
10
128
1
Order By: Relevance
“…Here we use an automated, homecage system for sensory association training (SAT) to 74 examine the laminar location and trajectory of changes in PV-mediated inhibition in primary 75 somatosensory (barrel) cortex during learning. Our prior studies have shown that excitatory 76 synaptic strengthening sequentially progresses across the cortical column during SAT, starting 77 in deep layers and progressing to superficial layers (Audette et al, 2019). In accordance with 78 the disinhibition hypothesis (Letzkus et al, 2015) , we predicted that PV disinhibition would be 79 initiated in deep layers, where thalamic input potentiation is first observed, and would then 80 proceed to superficial layers prior to the emergence of excitatory strengthening there.…”
Section: Introduction 40supporting
confidence: 59%
See 2 more Smart Citations
“…Here we use an automated, homecage system for sensory association training (SAT) to 74 examine the laminar location and trajectory of changes in PV-mediated inhibition in primary 75 somatosensory (barrel) cortex during learning. Our prior studies have shown that excitatory 76 synaptic strengthening sequentially progresses across the cortical column during SAT, starting 77 in deep layers and progressing to superficial layers (Audette et al, 2019). In accordance with 78 the disinhibition hypothesis (Letzkus et al, 2015) , we predicted that PV disinhibition would be 79 initiated in deep layers, where thalamic input potentiation is first observed, and would then 80 proceed to superficial layers prior to the emergence of excitatory strengthening there.…”
Section: Introduction 40supporting
confidence: 59%
“…Our prior studies indicate that SAT drives progressive changes in anticipatory licking and 95 excitatory synaptic strength that are initiated early in the training period (Audette et al, 2019). 96…”
Section: Prolonged Sensory Association Training Reveals Multiple Stagmentioning
confidence: 97%
See 1 more Smart Citation
“…Primary and higher-order thalamocortical nuclei convey qualitatively different types of information 10,12,[18][19][20][21][22] , and we wondered if VP and POM communication with TRN might involve parallel differences in synaptic processing mechanisms. To address this, we compared the dynamic features of the glutamatergic synaptic currents (kinetics and short-term synaptic depression) evoked by photostimulating VP and POM inputs to central and edge TRN cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A potential mechanism of this is that disinhibition of apical dendritic spikes leads to long-term potentiation of local recurrent synapses among cortical pyramidal neurons (Williams and Holtmaat, 2019). Furthermore, an in vivo study found that associative learning can also potentiate long-range POm connections onto pyramidal neurons when subsequently measured in vitro (Audette et al, 2019). Future studies are needed to address the links between arousal, attention, and plasticity.…”
Section: Discussionmentioning
confidence: 99%